Effectiveness of analgesic ear drops as add-on treatment to oral analgesics in children with acute otitis media: study protocol of the OPTIMA pragmatic randomised controlled trial. Issue 2 (22nd February 2023) - de Sévaux, Joline L H; Damoiseaux, Roger A M J; Hullegie, Saskia; Sanders, Elisabeth A M; de Wit, G Ardine; Zuithoff, Nicolaas P A; Yardley, Lucy; Anthierens, Sibyl; Little, Paul; Hay, Alastair D; Schilder, Anne G M; Venekamp, Roderick P
Abstract : Introduction: Ear pain is the most prominent symptom of childhood acute otitis media (AOM). To control the pain and reduce reliance on antibiotics, evidence of effectiveness for alternative interventions is urgently needed. This trial aims to investigate whether analgesic ear drops added to usual care provide superior ear pain relief over usual care alone in children presenting to primary care with AOM. Methods and analysis: This is a pragmatic, two-arm, individually randomised, open, superiority trial with cost-effectiveness analysis and nested mixed-methods process evaluation in general practices in the Netherlands. We aim to recruit 300 children aged 1–6 years with a general practitioner (GP) diagnosis of AOM and ear pain. Children will be randomly allocated (ratio 1:1) to either (1) lidocaine hydrochloride 5 mg/g ear drops (Otalgan) one to two drops up to six times daily for a maximum of 7 days in addition to usual care (oral analgesics, with/without antibiotics); or (2) usual care. Parents will complete a symptom diary for 4 weeks as well as generic and disease-specific quality of life questionnaires at baseline and 4 weeks. The primary outcome is the parent-reported ear pain score (0–10) over the first 3 days. Secondary outcomes include proportion of children consuming antibiotics, oral analgesic use and overall symptom burden in the first 7 days; number of days with ear pain, number of GP reconsultations and subsequent antibiotic prescribing, adverse events, complications of AOM and cost-effectiveness during 4-week follow-up; generic and disease-specific quality of life at 4 weeks; parents' and GPs' views and experiences with treatment acceptability, usability and satisfaction. Ethics and dissemination: The Medical Research Ethics Committee Utrecht, the Netherlands, has approved the protocol (21-447/G-D). All parents/guardians of participants will provide written informed consent. Study results will be submitted for publication in peer-reviewed medical journals and presented at relevant (inter)national scientific meetings. Trial registration: The Netherlands Trial Register: NL9500; date of registration: 28 May 2021. At the time of publication of the study protocol paper, we were unable to make any amendments to the trial registration record in the Netherlands Trial Register. The addition of a data sharing plan was required to adhere to the International Committee of Medical Journal Editors guidelines. The trial was therefore reregistered in ClinicalTrials.gov (NCT05651633 ; date of registration: 15 December 2022). This second registration is for modification purposes only and the Netherlands Trial Register record (NL9500) should be regarded as the primary trial registration.